Comparison of PD-L1 mRNA Expression Measured with the CheckPoint Typer® Assay with PD-L1 Protein Expression Assessed with Immunohistochemistry in Non-small Cell Lung Cancer - Erber, Ramona; Stoehr, Robert; Herlein, Stefanie; Giedl, Claudia; Rieker, Ralf; Fuchs, Florian; Ficker, Joachim H.; Hartmann, Arndt; Veltrup, Elke; Wirtz, Ralph M.; Brueckl, Wolfgang M. (Anticancer Research, 2017)
Immunohistochemical (IHC) assessment of programmed death-ligand 1 (PD-L1) in non-small cell lung cancer (NSCLC) has become important since the development of anti-PD-1/-PD-L1 directed drugs. Various PD-L1 antibodies and cut-offs have been used in different trials to predict response to these drugs, thus comparison of those studies is difficult. We compared PD-L1 mRNA expression measured by RT-qPCR with PD-L1 protein expression evaluated by IHC. Moreover, we investigated the impact of different tumour tissue acquisition methods on the reliability of PD-L1 measurement techniques.NSCLC cases (N=22), including n=9 mediastinal lymph node biopsies acquired by endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) and n=5 metastases, were evaluated prospectively for PD-L1 protein on tumor cells (TC) and immune cells (IC) using E1L3N and 28-8 antibodies and PD-L1 mRNA using the CheckPoint TYPER® assay.In primary NSCLC tissues, agreement between PD-L1 mRNA and TC staining using the 28-8 antibody was excellent (?=0.85, p=0.0002). Comparing both PD-L1 antibodies against each other showed a kappa value of 0.58 (p=0.0106). In EBUS-TBNA, PD-L1 mRNA correlated perfectly with the 28-8 antibody (?=1.0, p=0.0023). PD-L1 mRNA levels significantly differed when comparing 28-8 TC staining of tumours >49% with 1-49% and 0% (p=0.0040; p=0.0081, respectively). In metastatic lesions, differences between PD-L1 mRNA and IHC became apparent (?=0.2, p=0.2525).Testing of PD-L1 mRNA and 28-8 IHC showed an excellent agreement in NSCLC samples including mediastinal lymph node biopsies. Since PD-L1 expression in >50% TC detected by 28-8 IHC can be reliably detected by RT-qPCR, quantitative PD-L1 mRNA determination should be considered as an alternative to IHC as there is no interobserver variability in RNA results.
EVALuna2:6916